2014
DOI: 10.1016/j.abb.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

MAGE proteins regulate KRAB zinc finger transcription factors and KAP1 E3 ligase activity

Abstract: Expression of Melanoma AntiGen Encoding (MAGE) genes, particularly MAGE-A3, has been correlated with aggressive clinical course, the acquisition of resistance to chemotherapy and poor clinical outcomes of melanoma and other malignancies. MAGE proteins bind to KAP1, a gene repressor and ubiquitin E3 ligase which also binds KRAB domain containing zinc finger transcription factors (KZNFs), and MAGE expression may affect KZNF mediated gene regulation. To investigate mechanisms for these effects, we tested the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, qRT-PCR of ZNF224 after CPT treatment did not induce any change of ZNF224 mRNA level (data not shown), which suggests a possibility that DNA damage signal may induce degradation of ZNF224 by post-translational modification such as ubiquitination. It is well known that KRAB domain and it's neighboring amino acid sequences are critical to ubiquitination of KRAB-ZFPs [ 42 43 ]. Interestingly, KAP1 binds to KRAB domain of KRAB-ZFPs to function as an ubiquitin E3 ligase [ 43 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, qRT-PCR of ZNF224 after CPT treatment did not induce any change of ZNF224 mRNA level (data not shown), which suggests a possibility that DNA damage signal may induce degradation of ZNF224 by post-translational modification such as ubiquitination. It is well known that KRAB domain and it's neighboring amino acid sequences are critical to ubiquitination of KRAB-ZFPs [ 42 43 ]. Interestingly, KAP1 binds to KRAB domain of KRAB-ZFPs to function as an ubiquitin E3 ligase [ 43 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that KRAB domain and it's neighboring amino acid sequences are critical to ubiquitination of KRAB-ZFPs [ 42 43 ]. Interestingly, KAP1 binds to KRAB domain of KRAB-ZFPs to function as an ubiquitin E3 ligase [ 43 44 ]. In another study, it has been reported that the expression of KAP1 and KRAB-ZFPs was increased in breast carcinoma, and sumoylated-KAP1 protects the KRAB-ZFPs from proteasomal degradation, which promotes proliferation and metastatic progression of breast cancer cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, MAGEs can stimulate TRIM28 auto-ubiquitination and ubiquitination of substrates, such as p53 and ZNF382, leading to their degradation by the proteasome (18, 33, 34). In addition, MAGE-A1 and MAGE-G1 can stimulate the ligases activity of their cognate E3 RING ligase, TRIM31 and NSE1, respectively (18, 32).…”
Section: Mage-ring Ligases (Mrls)mentioning
confidence: 99%
“…Rather, each MAGE protein appears to recognize a unique region on its RING partner, suggesting that MAGE proteins are able to function as a versatile and adaptable protein interaction module. MAGE-A3 was found to interact with the nuclear scaffolding protein and E3 ligase TRIM28 (also known as KAP1), via its RING-B box coiled coil (RBCC) motif [ 15 ], and this interaction was found to stimulate the E3 ligase activity leading to degradation of various targets with roles in apoptosis such as the tumour suppressor p53[ 15 , 17 ], the KRAB zinc finger transcription factor ZNF382[ 18 ], and the metabolic regulator AMP activated protein kinase (AMPK)[ 14 ]. In contrast to MAGE-A3, relatively little is known about the possible interactions of MAGE-A4 with RING containing ligases.…”
Section: Introductionmentioning
confidence: 99%